Strategi Hotel Lombok Astoria Dalam Mempertahankan Citra di Masa Pandemi Covid-19 - Dhety Chusumastuti; Elizabeth Avelia Poereta (Pusat Riset dan Inovasi Nasional, 2022)
The hospitality industry in Indonesia, especially Lombok Island, continues to grow. This is due to the large number of both local and foreign tourists visiting Lombok Island. The demand for temporary housing or hotels has also increased, accompanied by the addition of tourists. However, the COVID-19 pandemic has made tourist numbers unstable or fluctuating. Hotels need a strategy to survive in this situation. One strategy to maintain the number of occupancy of a hotel is to maintain a good image. Image has an important role in hotel operations so it needs to be maintained and developed. One of the well-known hotels on Lombok Island is the Lombok Astoria Hotel with four stars. Lombok Astoria Hotel has a motto When Hospitality Blends With Business and Leisure, this motto is a hotel guide to achieving and maintaining the desired image. Thus, the purpose of this research is to find out and analyze the strategies implemented by Hotel Lombok Astoria in maintaining its image. This study uses qualitative research methods and data collection techniques by means of interviews, observation, and documentation. The results of this study indicate that Hotel Lombok Astoria has an effective strategy in maintaining its image.